Fiducial-free CyberKnife stereotactic body radiation therapy (SBRT) for single vertebral body metastases: acceptable local control and normal tissue tolerance with 5 fraction approach - Gill, Beant S.; Oermann, Eric K.; Ju, Andrew W.; Suy, Simeng; Yu, Xia; Rabin, Jennifer; Kalhorn, Christopher; Nair, Mani N.; Voyadzis, Jean-Marc; Unger, Keith; Collins, Sean; Harter, K.William; et al. (Frontiers in Oncology, 2012)
This retrospective analysis examines the local control and toxicity of five-fraction fiducial-free CyberKnife stereotactic body radiation therapy (SBRT) for single vertebral body (VB) metastases. All patients had favorable performance status (ECOG 0–1), oligometastatic disease, and no prior spine irradiation. A prescribed dose of 30–35 Gy was delivered in five fractions to the planning target volume (PTV) using the CyberKnife with X-sight spine tracking. Suggested maximum spinal cord and esophagus point doses were 30 and 40 Gy, respectively. A median 30 Gy (IQR, 30–35 Gy) dose was delivered to a median prescription isodose line of 70% (IQR, 65–77%) to 20 patients. At 34 months median follow-up (IQR, 25–40 months) for surviving patients, the 1- and 2-year Kaplan–Meier local control estimates were 80 and 73%, respectively. Two of the five local failures were infield in patients who had received irradiation to the gross tumor volume and three were paravertebral failures just outside the PTV in patients with prior corpectomy. No local failures occurred in patients who completed VB radiation alone. The 1- and 2-year Kaplan–Meier overall survival estimates were 80 and 57%, respectively. Most deaths were attributed to metastatic disease; one death was attributed to local recurrence. The mean maximum point doses were 26.4 Gy (SD, 5.1 Gy) to the spinal cord and 29.1 Gy (SD, 8.9 Gy) to the esophagus. Patients receiving maximum esophagus point doses greater than 35 Gy experienced acute dysphagia (Grade I/II). No spinal cord toxicity was documented. Five-fraction fiducial-free CyberKnife SBRT is an acceptable treatment option for newly diagnosed VB metastases with promising local control rates and minimal toxicity despite the close proximity of such tumors to the spinal cord and esophagus. A prospective study aimed at further enhancing local control by targeting the intact VB and escalating the total dose is planned.